The Effect of Green Investment, Leverage, And Profitability on Earnings Management (An Empirical Study of Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020-2024) - Rahayu Dwi Suryaningrum; Nasiti Rizky Shiyammurti (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
This study aims to analyze the effect of green investment, leverage, and profitability on earnings management in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study uses a quantitative approach with purposive sampling techniques and obtains 65 company observations. Earnings management is measured using discretionary accruals based on the Modified Jones Model. Green investment is proxied by the ratio of environmental expenditure to total assets, leverage by the Debt to Assets Ratio (DAR), and profitability by Return on Assets (ROA). The analysis is conducted using panel data regression with the Random Effect Model. The results show that green investment, leverage, and profitability simultaneously have a significant effect on earnings management. Partially, green investment has a negative but insignificant effect, leverage has no significant effect, while profitability has a positive and significant effect on earnings management.